Auroral zone plasma waves detected at polar: PCBL waves - Tsurutani, B.T.; Arballo, J.K.; Galvan, C.; Zhang, L.D.; Lakhina, G.S.; Hada, T.; Pickettd, J.S.; Gurnettd, D.A. (My University, 2001)
Polar Cap Boundary Layer waves are ELF/VLF electric and magnetic waves detected on field lines adjacent to the polar cap, thus their name. Waves are present at this location 96% of the time. The wave latitude-local time distribution is shown to be the same as that of the auroral oval. The most intense waves are detected coincident with the strongest magnetic field gradients (field-aligned currents). Specific frequency bands of whistler mode-waves are identified: ∼200 Hz, 1–2 kHz and ∼5 kHz. Two types of intense electric waves are present: solitary bipolar pulses (electron holes) and ∼kHz electric turbulence. The PCBL waves are most likely a consequence of auroral zone field-aligned current instabilities. The currents have in turn been ascribed to be due to magnetospheric convection driven by the solar wind.
Keywords: Magnetosphere; ELF/VLF waves; Magnetic waves; Auroral field; Magnetic field; Plasma waves; PCBL waves; Solar wind